Linguistic Autonomy of EU Institutions, Bodies and Agencies - van der Jeught, Stefaan (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
This article aims at shedding some light on both explicit and implicit internal language arrangements and practices which currently exist in the various EU institutions, bodies and agencies. It will be shown that they enjoy in effect a large “linguistic autonomy” to determine their own internal language arrangements. The legal basis of this linguistic autonomy will be discussed, as well as the ensuing internal language policies which have been explicitly or implicitly established.The author is Press officer at the Court of Justice of the European Union and Visiting Professor of European Law at the Vrije Universiteit Brussel (Belgium). His contribution reflects only personal views.